Probing the Impedance of a Biological Tissue with PEDOT:PSS‐Coated Metal Electrodes: Effect of Electrode Size on Sensing Efficiency. Issue 23 (8th November 2019) - Koutsouras, Dimitrios A.; Lingstedt, Leona V.; Lieberth, Katharina; Reinholz, Jonas; Mailänder, Volker; Blom, Paul W. M.; Gkoupidenis, Paschalis
Abstract: Electrodes coated with poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) have been employed to measure the integrity of cellular barriers. However, a systematic experimental study of the correlation between tissue integrity and impedance of the sensing device has not yet been conducted. Using impedance spectroscopy, how the impedance ratio of the biological tissue to the recording device affects the recording ability of the latter is investigated. PEDOT:PSS‐coated electrodes of various dimensions are employed and the effect of their size to their sensing efficiency is examined. The biotic/abiotic ensemble is modeled with a simple equivalent circuit and an analytical expression of the total impedance as a function of frequency is extracted. The results reveal a critical impedance ratio of the biological tissue to the sensor which allows for efficient sensing of the tissue integrity. This work provides the ground rules for improved impedance‐based biosensors with optimized sensitivity. Abstract : Despite the extended use of poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate devices on probing the integrity of cellular barriers, the correlation between their impedances on the sensing efficiency is not yet systematically investigated. This work discloses this impedance interplay with the use of impedance spectroscopy, resulting in design rules for the optimization of conducting polymer‐based biosensors.